Creation Music Grebeg Singasari | Tabuh Kreasi Grebeg Singasari - Kumara Dinata I Putu Agus; I Made Kartawan (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Grebeg Singasari is a tradition that acts as a universal observer with the concept of authenticity breaking through the boundaries of space which leads to the pancer of Pura Luhur Giri Kusuma. Ngerebeg is a tradition that is carried out routinely on Umanis Kuningan or Reditte Umanis Wuku Langkir and is still being held to this day and has been passed down from generation to generation by the people of Blahkiuh Village. The ngerebeg tradition is carried out at Luhur Giri Kusuma Temple which is located in the center of Blahkiuh Village or more precisely to the west of Blahkiuh market which is the Dhang Kayangan Temple which is served by almost all people in Badung Regency. In this work the spoken media used is Barungan Gamelan Selonding and combined with other supporting instruments such as one pair of Krumpungan drums, one pair of Pepanggulan drums, one Kajar Renteng, one Kecek (Cengceng ricik), one Gong, one Kempur, one Klemong fruit, one Gentorang fruit, four Suling fruit, and two singers (Gerong). In the production of this work, no longer uses the tri angga structure, but uses sections, each of which depicts the procession of the Ngerebeg tradition. The creation of this work uses the creation method of M. Hawkins in his book Creating Through Dance which is discussed by Y.Sumandiyo Hadi ISI Yogyakarta, 1990. Hawkins mentions 3 stages of the process of creating works of art, namely: the Assessment stage (Exploration), the Experimental stage (Improvisation), and finally the Forming stage.